Revisiting the Latvian and Greek financial crises: The benefits of front-loading Fiscal adjustment - Anders Åslund (Center for Social and Economic Research (CASE), 2015)
This paper discusses why Greece has done so poorly in comparison with all other European Union countries since the onslaught of the global financial crisis in 2008. To show what was wrong with its fiscal adjustment, this paper compares Greece with the other European Union country that was hit be the most severe fiscal crisis, namely Latvia. The conclusion is that front-loaded fiscal adjustment works much better. Greek economic policy has been a popular topic among opinion writers, notably Nobel Prize winner and New York Times columnist Paul Krugman, who claimed that Greece suffered from austerity. Because of his prominence in the international public debate, I shall scrutinize his arguments on the Greek crisis. The paper also examines what policy the International Monetary Fund has pursued with regard to Greece, and how its views have been influenced by the debate and Greek economic developments. Finally, the paper assesses what lessons can be drawn from the contrasting experiences of Latvia and Greece. The conclusion is that a fiscal adjustment should be sufficient to resolve the crisis to restore confidence and that it should be as front-loaded as is practically and politically possible.
Keywords: E60; E62; 330; Macroeconomic policy; fiscal policy; fiscal adjustment; austerity; Greece; Latvia; International Monetary Fund